Agronomic characteristics of 30 promising lines of aromatic, red, and black rice and their antioxidant and cytotoxic effects in some cancer cells - YUSUF LIMBONGAN; RICO RAMADHAN; KUNIYOSHI SHIMIZU; Enos Tangkearung (Society for Indonesian Biodiversity, 2021)
Abstract. Limbongan Y, Ramadhan R, Shimizu K, Arung ET. 2021. Agronomic characteristics of 30 promising lines of aromatic, red, and black rice and their antioxidant and cytotoxic effects in some cancer cells. Biodiversitas 22: 1695-1700. In our effort to increase rice production, some activities were done such as increased land production, rice planting patterns, and crossbreeding some rice with the special characteristic. We have cross-bred aromatic rice with red rice and black rice. These activities resulted in thirty lines of rice varieties. The thirty lines of rice variation were extracted with ethanol and evaluated the extracts for their phytochemicals, antioxidant activity, and cytotoxicity effect on cancer cell lines (MCF-7, HeLa, and OVK-18). The phytochemicals of thirty lines variation of rice showed variation in their contents. The line of F2BA201 extracts showed the strongest in antioxidant with IC50 2.43 ?g/mL while Vitamin C was 32.93 ?g/mL. The line of F2LD20 extracts displayed potent inhibition with value of 40.2% against OVK-18 cancer cells while 5FU as positive control revealed percentage inhibition with value of 21.2%. Based on the results, the thirty line rice variations exhibited antioxidant and anti-cancer potential.